Dose response of A/Alaska/6/77 (H3N2) cold-adapted reassortant vaccine virus in adult volunteers: role of local antibody in resistance to infection with vaccine virus. - Clements, M L (1983)
An attenuated influenza A candidate vaccine virus, derived from the A/Ann Arbor/6/60 (H2N2) cold-adapted (ca) donor virus and the A/Alaska/6/77 (H3N2) wild-type virus, was evaluated in adult seronegative volunteers (serum hemagglutination-inhibiting antibody titer, less than or equal to 1:8) for level of attenuation, infectivity, antigenicity, and genetic stability. Four groups with similar preinoculation mean titers of serum and nasal wash antibodies were inoculated intranasally with 10(4.5), 10(5.5), 10(6.5), or 10(7.5) 50% tissue culture infectious doses (TCID50) of the ca reassortant virus, and eight other seronegative adult volunteers received the wild-type virus. Only 2 of 66 vaccinees developed fever or mild and brief systemic or upper respiratory tract illness or both. Both volunteers with vaccine-related reactions received the highest dose (10(7.5) TCID50) of ca virus, which indicates that the vaccine retains some mild reactogenicity at a high dosage. In contrast, four of eight volunteers infected with the wild-type virus became ill. Each of the 54 isolates tested retained the temperature-sensitive phenotype of the vaccine virus. Thus, the ca reassortant was genetically stable and attenuated at 10(4.5) to 10(7.5) TCID50 for seronegative adults. The 50% human infective dose of ca virus was approximately 10(5.3) TCID50. Ten and one hundred 50% human infectious doses infected 73 and 83% of vaccinees, respectively, and approximately 75% developed an immunological response at these doses. The failure of the vaccine virus to infect some volunteers was correlated with the presence of pre-inoculation nasal wash immunoglobulin A hemagglutinin antibody.